Synthesis of Symmetrical N-Aryl-C-phosphonoacetamidines - Erkhitueva, Elena B.; Panikorovskii, Taras L.; Svintsitskaya, Nataly I.; Trifonov, Rostislav Е.; Dogadina, Аlbina V. (Synlett, 2018)
An efficient synthesis of a series of novel symmetrical N-aryl-C-phosphonoacetamidines through reaction of diisopropyl (chloroethynyl)phosphonate with primary aryl amines was developed. This procedure tolerates a wide range of functional groups and has a good atom economy. The (E)-isomer was the major product that crystallized preferentially over the (Z)-isomer.
Keywords: aryl amidines; carbamimidoylphosphonoacetic acid; aryl amines; phosphonoacetamidines